1970
DOI: 10.31729/jnma.2263
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Nasogastric Decompression after Emergency Laparotomy

Abstract: Introduction: Post-operative nasogastric intubation after emergency laparotomy is a commonpractice in many centers, with the intent of hastening the return of bowel function, relievinggastrointestinal discomfort, reducing various post-operative complications and reducing hospitalstay. However, bowel rest and gastric decompression have been re-examined in the light of morerecent data. Many studies and meta-analyses over the last 50 years have challenged the routine useof nasogastric tubes after laparotomy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Meanwhile, risk factors for NGT reinsertion were left-sided colon cancer, postoperative ileus and severe postoperative complications[38]. A randomized controlled trail examining the effect of prophylactic NGT decompression after emergency laparotomy for generalized peritonitis and intestinal obstruction indicated that routine NGT insertion did not prevent gastrointestinal discomfort or anastomotic leakage[39].…”
Section: Application Of Eras Items In Emergency Colorectal Surgery Anmentioning
confidence: 99%
“…Meanwhile, risk factors for NGT reinsertion were left-sided colon cancer, postoperative ileus and severe postoperative complications[38]. A randomized controlled trail examining the effect of prophylactic NGT decompression after emergency laparotomy for generalized peritonitis and intestinal obstruction indicated that routine NGT insertion did not prevent gastrointestinal discomfort or anastomotic leakage[39].…”
Section: Application Of Eras Items In Emergency Colorectal Surgery Anmentioning
confidence: 99%
“…Forced expiratory volume (1 second/forced vital capacity); 18 45. 17,19,24,[26][27][28]31,32,35,36,[41][42][43][44]48,51,54,57,60,65,67 47. Recurrences submitted to surgery/reoperation; 17,19,22,29,32,35,36,44,57 48.…”
Section: Duration Of IV Therapy 45mentioning
confidence: 99%
“…Time to recurrence; 24,44,57 50. Recurrence free survival 44,54,57 Wound infection 18,21,[23][24][25][27][28][29]33,35,46,48,52 13 (25.4)…”
Section: Duration Of IV Therapy 45mentioning
confidence: 99%
“…The advent of new guidelines and pathway driven care has resulted in fewer morbidities and shorter hospitalizations [ 65 ] [ 66 ]. Several studies dating back to 1995 report the benefits of forgoing the traditional practices of postoperative gastric decompression for the management of laparotomy, gastrectomy and minimally invasive esophagectomy patients [ 67 ] [ 68 ] [ 69 ]. Its routine use has even been questioned in the management of small bowel obstructions [ 70 ].…”
Section: Discussionmentioning
confidence: 99%